The possibilities of utilising the skiddometer T2GO for forensic engineering - Tomáš Kohout; Pavel Vrtal; Adam Hoffmann; Tomáš Blodek (Acta Polytechnica CTU Proceedings, 2023)
The aim of the paper is to verify the applicability of the T2GO skiddometer for measuring the coefficient of friction for forensic practice in accordance with the legislative framework of the Czech Republic. In the introduction, the article discusses the problem of friction coefficient measurement. The results of the comparison with dynamic measuring devices used in the Czech Republic and the determination of the mutual compliance rate with these devices, based on data obtained within the National Comparative Measurement Action, are presented. The article concludes with an interpretation and discussion of the results. In cases where no sufficient mutual compliance was found, an analysis and reasoning of these results is provided. Last but not least, based on the results, a procedure is proposed for future use of the T2GO skiddometer in practice within the legislative conditions of the Czech Republic.